Low Temperature Catalytic Hydroxylation of Benzene to Phenol over SBA-15 as Supported Catalysts Under Microwave Irradiation - Liu, Tong; Hou, Jinhui; Peng, Yaoli (Asian Journal of Chemistry, 2015)
Liquid phase hydroxylation of benzene to phenol with hydrogen peroxide over catalysts prepared by the metallic compounds [e.g., Fe(III), Cu(II), Co(II)] impregnated on SBA-15 was investigated at room temperature under microwave irradiation. This paper studied the catalytic performances of SBA-15 supports prepared by the various calcined temperature and time. The catalysts were characterized by N2 adsorption technique. The Fe(III)/SBA-15 catalyst gave the highest conversion and yield than Cu(II), Co(II)/SBA-15 at same experimental condition. Various reaction parameters, such as amount of catalyst, amount of hydrogen peroxide and reaction time were investigated to obtain an optimal reaction conditions for phenol formation under microwave irradiation. Coupled conventionally heated method gives phenol yield of 8.9 %, the Fe(III)/SBA-15 gives higher phenol yield of 18.3 % and selectivity of 100 % under microwave irradiation conditions.